Faktor-Faktor Yang Mempengaruhi Kepuasan Pegawai Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Pati - Dwi Rahayu; Qristin Violinda; Ira Setiawati (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The purpose of this study is to determine the effect of information quality, information systems and the quality of service interaction on employee satisfaction. This research took the object of 50 employees of the Investment and One-Stop Integrated Services Office of Pati Regency. The researcher's sampling technique uses saturated sampling. Data analysis method using multiple regression The results of the study found that there was a positive and significant influence of information quality on employee satisfaction, there was a positive and significant influence of information systems on employee satisfaction and there was a positive and significant influence on the quality of service interaction on employee satisfaction.